Small Bowel Angiodysplasia Managed with Novel Motorized Spiral Enteroscope: A Case Report - Kothakota, Sunil Raviraj; Sasidharan, Madhu; Kareem, Harish; Nair, Ajith K. (Journal of Digestive Endoscopy, 2020)
We report a case of 72-year-old woman, who presented with complaints of melena associated with shortness of breath on exertion for more than 2 weeks. On evaluation, she was diagnosed to have severe anemia with evidence of occult blood in stool. After initial management, further workup was done to find out the source of bleeding. Upper and lower gastrointestinal endoscopy were normal. Computerized tomography enteroclysis showed no significant abnormality. Later small bowel enteroscopy was performed with the help of Novel Motorized Spiral Enteroscope in antegrade approach and scope passed through oral cavity up to cecum. Multiple angiodysplasia lesions seen in ileum. All the lesions were managed with argon plasma coagulation (APC). Postprocedure, patient improved well and hemoglobin also remained stable. Small bowel diseases always remain a diagnostic and therapeutic challenge, despite the introduction of various modalities for deep enteroscopy. Spiral enteroscopy is a recent advance which uses an overtube with a raised spiral at the distal end to pleat the small intestine. It consumes less time and suits for both diagnostic and therapeutic needs of small bowel diseases.
Keywords: small bowel bleed; ileal angiodysplasia; spiral enteroscope